2009
DOI: 10.1042/cs20080272
|View full text |Cite
|
Sign up to set email alerts
|

RGS proteins: identifying new GAPs in the understanding of blood pressure regulation and cardiovascular function

Abstract: Understanding the mechanisms that underlie BP (blood pressure) variation in humans and animal models may provide important clues for reducing the burden of uncontrolled hypertension in industrialized societies. High BP is often associated with increased signalling via G-protein-coupled receptors. Three members of the RGS (regulator of G-protein signalling) superfamily RGS2, RGS4 and RGS5 have been implicated in the attenuation of G-protein signalling pathways in vascular and cardiac myocytes, as well as cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
56
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 79 publications
(113 reference statements)
0
56
0
3
Order By: Relevance
“…Moreover, we identified a conserved cAMP-response element (CRE) in the murine RGS2 promoter that is critical for cAMP-response element-binding protein (CREB) binding and RGS2 promoter activation. Forskolin-stimulated RGS2 mRNA up-regulation is inhibited by CREB sequestration or specific disruption of the CREB-RGS2 promoter interaction, and Ang IIinduced CREB phosphorylation and nuclear localization are blocked by iPLA 2 ␤ pharmacologic inhibition or genetic ablation. Ang II-induced intracellular cyclic AMP accumulation precedes CREB phosphorylation and is diminished by inhibiting iPLA 2 , cyclooxygenase, or lipoxygenase.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, we identified a conserved cAMP-response element (CRE) in the murine RGS2 promoter that is critical for cAMP-response element-binding protein (CREB) binding and RGS2 promoter activation. Forskolin-stimulated RGS2 mRNA up-regulation is inhibited by CREB sequestration or specific disruption of the CREB-RGS2 promoter interaction, and Ang IIinduced CREB phosphorylation and nuclear localization are blocked by iPLA 2 ␤ pharmacologic inhibition or genetic ablation. Ang II-induced intracellular cyclic AMP accumulation precedes CREB phosphorylation and is diminished by inhibiting iPLA 2 , cyclooxygenase, or lipoxygenase.…”
mentioning
confidence: 99%
“…RGS2 is expressed ubiquitously, and its major biological function is to serve as a GTPase-activating protein that preferentially attenuates heterotrimeric G protein G␣ q/11 GTPase activity (2). Several independent studies have demonstrated that Rgs2 knock-out mice have severe hypertension (3)(4)(5)(6)(7), suggesting that RGS2 plays a critical role in blood pressure homeostasis.…”
mentioning
confidence: 99%
See 3 more Smart Citations